2018
DOI: 10.7717/peerj.4266
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation and DNA fingerprinting of durian types in Malaysia using simple sequence repeat (SSR) markers

Abstract: Durian (Durio zibethinus) is one of the most popular tropical fruits in Asia. To date, 126 durian types have been registered with the Department of Agriculture in Malaysia based on phenotypic characteristics. Classification based on morphology is convenient, easy, and fast but it suffers from phenotypic plasticity as a direct result of environmental factors and age. To overcome the limitation of morphological classification, there is a need to carry out genetic characterization of the various durian types. Suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Additionally, the genetic diversity of olive accessions could be assessed based on newly developed SSR markers, and thus it is possible to select certain cultivars for hybridization to achieve new olive cultivars with potential usefulness. In recent years, DNA fingerprints have been successively established in many plants, such as chrysanthemum, oil camellia, durian, and pistachio (Zhang et al, 2014;Chen et al, 2016;Siew et al, 2018;Mannino, Gentile & Maffei, 2019). In the olive, DNA fingerprinting is considered very important because both the productivity and quality of olive products are intrinsic characteristics of the original cultivars (Muzzalupo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the genetic diversity of olive accessions could be assessed based on newly developed SSR markers, and thus it is possible to select certain cultivars for hybridization to achieve new olive cultivars with potential usefulness. In recent years, DNA fingerprints have been successively established in many plants, such as chrysanthemum, oil camellia, durian, and pistachio (Zhang et al, 2014;Chen et al, 2016;Siew et al, 2018;Mannino, Gentile & Maffei, 2019). In the olive, DNA fingerprinting is considered very important because both the productivity and quality of olive products are intrinsic characteristics of the original cultivars (Muzzalupo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that when the sample size was enlarged, the specific fragments of the single marker would lose their specificity. The application of single marker analysis to identify specific accessions from large samples would be thus restricted [34].…”
Section: Discussionmentioning
confidence: 99%
“…Fiber and minerals in fruit wastes, have been shown to be able to immobilize L. acidophilus cells during fermentation, which resulted in increased growth (Teh et al, 2009). In addition, many durian types are known to exist, which can be classified based on morphologic characteristics such as seed size and shape (Siew et al, 2018). We therefore extracted DSG from four durian types, with different seed shapes.…”
Section: Discussionmentioning
confidence: 99%